Teaching Arabic Language to Non-Native Speakers at Ali Bin Abi Talib Institute and Badr Al-Saleh Institute: A Comparative Study - Ahmad Naufal Saif; Durrotul Hasanah; Siti Maesaroh (Journal of Arabic Language Studies and Teaching, 2021)
This research aims to know the student's proficiency in the productive Arabic language skills, the skill of speaking and writing, and how the third-year students at the Ali bin Abi Thalib Islamic Institute in Surabaya outperformed the third-grade students at the Badr Al-Saleh Purwoasri Kediri Islamic Institute. In these two skills, a lot of students at the Ali Bin Talib Islamic Institute in Surabaya came from senior high school, and the students of the Badr Al-Saleh Institute Purwoasri came from Islamic schools. One of the extrapolations that the researcher uses in this scientific research is by case study, and the approaches that the researcher used in this research are the qualitative approach and the quantitative approach. And the skill that the researcher chose in this research is productive skills, the skill of speaking and writing.